Steoplastic Materials Used In Surgical Dentistry (Eurasian Medical Research Periodical, 2024)
Modern surgical dentistry faces an acute problem of bone tissue regeneration after inflammatory, traumatic diseases and extraction interventions, which lead to its deficiency. Physiological regeneration often does not produce the required volume of new bone. And local bone deficiency makes dental implantation difficult. There are different groups of materials that stimulate osteogenesis: autogenous, allogeneic, xenogeneic and synthetic. The osteoinductive potential, osteoconductive properties and tolerance by the tissues of the receiving bed are expressed differently in the groups. It is difficult for a clinician to choose an osteoplastic material with optimal parameters from the many offered options due to the wide variety of bone regeneration stimulators.